Custody and Visitation in Families With Three (or More) Parents. (24th July 2018) - Cahn, Naomi; Carbone, June
Abstract : New technological and legal developments have enabled the formation of three‐parent families. Now that these families have arrived, families—and family law—must adapt to allocate responsibilities among the responsible adults. Key Points for the Family Court Community: Identifies states permitting three‐parent families Demonstrates how family law allocates custody and visitation in these families Provides suggestions for reform